2023
DOI: 10.1371/journal.pone.0283677
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of protease from psychrotrophic Bacillus sp. HM49 in North-western Himalaya

Abstract: In this work, a psychrotrophic bacteria producing cold-active protease, was obtained from Dachigam National Park, an ecologically significant habitat in Western Himalayas owing to its varied endemic and endangered flora and fauna. This isolate was identified as Bacillus sp. HM49 via phenotypic, Gram staining, bio-chemical and 16S rRNA gene identification. Isolate HM49 when tested for proteolytic activity revealed prominent hydrolytic zone with the most production at 20 °C and pH, 8.0 post 72 h incubation. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…ASU1 and ASU isolates hydrolyze starch, casein and gelatin. ASU2 bacterial isolate was positive for methyl red test but not ASU1, this results shown similarity with the biochemical tests in this studies [11,52,53] which prove that ASU1 and ASU2 bacterial isolates are Bacillus species. For Sm-26 bacterial isolate the biochemical tests showed that it is Gram negative bacteria, short rodes and motile.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…ASU1 and ASU isolates hydrolyze starch, casein and gelatin. ASU2 bacterial isolate was positive for methyl red test but not ASU1, this results shown similarity with the biochemical tests in this studies [11,52,53] which prove that ASU1 and ASU2 bacterial isolates are Bacillus species. For Sm-26 bacterial isolate the biochemical tests showed that it is Gram negative bacteria, short rodes and motile.…”
Section: Discussionsupporting
confidence: 79%
“…Microbial proteases are favoured because they can be produced more easily than proteases from animal and plant sources, and have practically the whole qualities needed for their industrial uses [50].Alkaline proteases are mostly produced by microbes, particularly Bacillus species, since they have properties that make them suitable for use in a different industrial applications [51].In this study all 17 bacterial isolates which isolated from proteinacious sources are notable for their ability to produce protease enzyme. In contrast,Mushtaq, Ganai et al [52] found from screening for protease production ability of 15 bacterial isolates which were isolated from a grassland site in lower part of Dachigam National Park that out of them 8 isolates could produce protease enzyme. Similarly, Ali, Ullah et al [11] reported that 54 bacterial strains were isolated from salt mines of Karak, Pakistan, screened for their proteolytic activity and found that 23 isolates from them had proteolytic activity.…”
Section: Discussionmentioning
confidence: 94%